Dissemination of Breeding Technology at Hatchery Unit in XIII Koto Kampar District, Kampar Regency Riau Province - Yohana Frizia; Ridar Hendri; Kusai ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
This study was conducted on August in XIII Koto Kampar District, Kampar Regency Riau Province. This study aims to determine the general picture disseminated of breeding technology, process technology dissemination of breeding obtained by fish farmers, people or institutions that disseminate technology and problems in the process of disemination.The method used method case study.Objek of study methods is 3 hatchery unit and respondents of this research were owner hatchery .These hatcheries were Graha Pratama Fish in the Koto Mesjid and Akuafisha in the Pulau Gadang . The technology which disseminated were temperature shock technology , hatchery with funnel method , and application methods of fish hatchery. Source dissemination come from university, BBPBAT Sukabumi and Jambi. This Method of dissemination was training. Problems in the dissemination process was BBI Center and BBI Lokal not yet find a breeding technology. Beside it, indirect method dissemination such as using communication media was rarely, dissemination activities are rarely performed and participants in the dissemination should hatcheries certificateKaeyword : Dissemination, Seeding Technology and People’s Hatchery Unit